In Vitro and In Vivo Evaluation of the De Novo Designed Antimicrobial Peptide P6.2 Against a KPC-Producing P. aeruginosa Clinical Isolate - Martínez, Melina María Belén (2025)
The antimicrobial peptide P6.2 was previously de novo designed as an alpha hélix cationic amphipathic molecule. In previous work, we have shown that this peptide displayed significant antimicrobial activity against both Gram-positive (Staphylococcus aureus) and Gram-negative (Pseudomonas aeruginosa) bacteria. However, while P6.2 lacked biofilminhibiting properties against the P. aeruginosa strain PA01, it displayed anti-inflammatory effects in a murine acute lung infection model challenged with this pathogen. In this work, the peptide P6.2 antimicrobial activity and its possible synergy with meropenem were evaluated both in vitro and in vivo using a Galleria mellonella infection model against a carbapenem-resistant KPC-producing clinical isolate of P. aeruginosa. Firstly, the cytotoxic effect of the peptide on A549 and RAW264.7 cell lines was assayed, showing no cytotoxicity at 64 μg/mL and below. Then, the MIC (minimal inhibitory concentration) and bactericidal effect against the carbapenemase-producing strain P. aeruginosa M13513 strain were determined. P6.2 showed a MIC between 32 and 64 μg/mL, and a rapid bactericidal activity against this strain (less than 45 min). The peptide stability at different temperaturas and in bovine serum at 37 ◦C was also analyzed, showing good stability and almost no degradation after 15 min of incubation at 100 ◦C or 24 h at 37 ◦C in serum, respectively. The antibiofilm activity was also evaluated, and although the peptide did not show biofilm inhibitory activity, it did demonstrate biofilm disruptive activity, together with bactericidal activity inside the pre-formed biofilm. The possible synergistic effect with the carbapenem meropenem was then analyzed in vitro by killing kinetics, revealing a synergistic interaction between P6.2 and the antibiotic against this strain. Finally, P6.2 was evaluated in vivo in the Galleria mellonella larvae infection model. Interestingly, in G. mellonella, P6.2 alone did not completely clear the infection caused by P. aeruginosa M13513. However, when combined with meropenem, P6.2 demonstrated a synergistic effect, leading to increased survival rates in infected larvae. The results presented here highlight the potential that this peptide displays when used in combination with carbapenems against a clinically relevant KPC-producing P. aeruginosa.